The Influence of Traditional Chinese Aesthetics on the Improvement of Aesthetic Musical Abilities - Gong, Jiani; Daoruang, Krisada (Journal of Ecohumanism, 2024)
Music is a meaningful way to implement aesthetic education and an essential part of aesthetic education. This study aimed to study which traditional Chinese aesthetic ideas are essential in enhancing aesthetic emotions to determine which important traditional aesthetic thoughts influence the improvement of people's aesthetic connotation. The scope of the research is to systematically classify traditional Chinese aesthetic knowledge and explore the factors that influence the improvement of aesthetic ability. The focus of the interview is on how college students can improve their aesthetic inspiration when appreciating Chinese music works from the aesthetic factors of Chinese aesthetics, such as the beauty of the conception, the beauty of the situation, and the beauty of rhyme so that they can not only "entertain their ears" but also "empathize" after listening to music. The findings emphasize that traditional Chinese aesthetics seeks emptiness, charm, profundity, artistic conception, and vividness, emphasizing intuition and comprehension. This spiritual core can nourish people's emotions and enhance aesthetic emotions.